YOUTH SPIRITUALITY IS THE FOUNDATION OF SOCIETY'S DEVELOPMENT - Khudaiberdiyeva Khuriyat Karimberdiyevna (Bright Mind Publishing, 2025)
This article outlines the ideas of educating selfless and patriotic youth with high spirituality, a firm life position, and a broad worldview, as a result of the reforms being implemented in our country today in the spiritual and educational sphere, protecting them from the influence of foreign ideas, and educating them in the spirit of loyalty to national and universal values, religious tolerance, and interethnic harmony.
Keywords: Spirituality, culture, patriotic spirit, education, upbringing, youth, nation, values, tolerance.